Bulbophyllum guniuensis (Orchidaceae: Epidendroideae; Malaxideae), a new species from Eastern China - Zhang, Si-Yu; Zhu, Ke-Run; Yan, Qi; Wu, Wei; Wang, Bo-Rui; Ni, Wei-Yong; Shao, Jian-Wen (Phytotaxa, 2022)
Bulbophyllum guniuensis W.Y. Ni & J.W. Shao, a new species of Orchidaceae from Anhui Province, eastern China, is described and illustrated. This new species is similar to B. henanense in overall plant size and leaf morphology, but differs from the latter by the length of the scape and the morphology of the lateral sepals and lip. B. guniuensis is also similar to B. hirundinis in margin fimbriate-ciliate, 3-veined dorsal sepal and petals, but differs from it in oblique oblong (vs. linear) lateral sepals and pale yellow to orange yellow (vs. purplish-red to yellow) flowers.